Numerical study of terahertz radiations from difference frequency generation with large spectral tunability and significantly enhanced conversion efficiencies boosted by 1D leaky modes. (22nd September 2022) - Jiang, Hui; Han, Zhanghua
Abstract: The nonlinear optical process of difference frequency generation (DFG) is a prominent technique to produce continuous-wave terahertz radiations while its low conversion efficiency calls for substantial enhancement using artificial structures. All-dielectric nanostructures supporting the quasi-bound states in the continuum (QBIC) appear as a promising approach to this end. To achieve the utmost of enhancement, both input lightwaves of the DFG should work at the QBIC conditions and in many cases a spectral tunability of the input wavelength is necessary. All these requirements go beyond the capability of conventional QBIC which can only happen within a narrow bandwidth for a given structure. In this work, we numerically demonstrate that these restrictions can be eliminated by using our recently proposed concept of one-dimensional leaky modes with ultrahigh Q factors and large operation bandwidth. Using an elaborately designed structures in the form of binary waveguide gratings (BWGs) made from LiNbO3 thin film, we demonstrate that a conversion efficiency enhanced by the order of 10 11 can be achieved using the BWGs made from LiNbO3, compared to the case of a bare LiNbO3 thin film. Furthermore, enhanced THz generations over a large spectral range can be easily achieved by changing the incident angle of one input light beam while tuning its wavelength to match the requirement for the leaky resonance excitation at that angle.